The Effect of Compensation and Transformational Leadership on Turnover Intention and Its Impact on Employee Performance at PT Waskita Concrete Precast Tbk - Subekhi Subekhi; Daman Sudarman (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The objective of this research is to examine how compensation and transformational leadership influence employees' intent to leave their jobs and how this affects their performance at PT Waskita Beton Precast Tbk. The research in this study utilizes a method of exploration with a numerical perspective to investigate how compensation and leadership impact turnover intention and performance among employees of PT Waskita Beton Precast Tbk. The information was gathered by distributing surveys to 240 participants chosen intentionally, and it was analyzed using SEM-PLS. Findings indicated that compensation and leadership have a moderate impact on employee productivity, with turnover intention playing a role as an intermediary, despite its limited effect on turnover intention and performance. On the employee performance variable, the R² value is 38.1%, which indicates that compensation and transformational leadership have a moderate influence on employee performance. For the turnover intention variable, the R² only reached 1.5%, which indicates a weak influence. The structural model used shows that turnover intentions act as a weak mediator of the effect of compensation and transformational leadership on employee performance. Further evaluation shows that the model has little GoF (Goodness of Fit), with a Q² value for employee performance of 20.5% and for turnover intentions of 0.4%, indicating that the model has limited predictive relevance.